Training (Medical) Interpreters—the Key to Good Practice. MedInt: A Joint European Training Perspective - Anita Ertl Sonja Pöllabauer (JoSTrans: The Journal of Specialised Translation)
After a short description of some of the basic aspects of community interpreter training, different training options for community interpreter training in general and healthcare interpreter training in particular, the paper presents an EU-funded project (Grundtvig/Lifelong Learning Programme) which focused on developing a curriculum for medical interpreting (MedInt—Development of a Curriculum for Medical Interpreters). The MedInt project was a multinational cooperation project funded by the European Commission as part of the Lifelong Learning Programme under the Grundtvig subprogramme. Between 2007 and 2009 the project consortium jointly developed a sample curriculum for medical interpreting, designed teaching materials and concentrated on awareness raising and dissemination initiatives in the partner countries. In this paper, the authors summarise the project objectives and the outline of the curriculum developed under MedInt.